The Politics of Service US-amerikanische Quäker und internationale humanitäre Hilfe 1917-1945 - Maul, Daniel (De Gruyter, 2021)
This is the first comprehensive history of the American Friends Service Committee (AFSC), the central humanitarian assistance organization of American Quakers during the first half of the 20th century. It describes the creation of a "humanitarian marketplace," the development of humanitarian techniques in relation to the media, donors, and recipients, as well as the complex relationship between religious and secular elements.